Surviving Data Breaches: A Multiple Case Study Analysis - Shankar, Nithya; Mohammed, Zareef (Journal of Comparative International Management)

(untitled) (Management Futures, 2020)
This study examines how organizations could potentially overcome the fallout of data breaches and achieve competitive advantage, by enhancing key firm capabilities through the process of sensing threats, seizing opportunities, and transforming/reconfiguring their existing resource base. We use the dynamic capabilities framework as the theoretical basis for this study. A multiple case study approach is applied to this study, using secondary data from the case studies of Target, Anthem, and Yahoo data breaches. Our findings indicate that utilizing the dynamic capability framework and its orchestration processes of sensing, seizing, and transforming/reconfiguring the resource base worked favorably in the case of Target and Anthem. However, for Yahoo, failure to utilize the aforementioned framework and orchestration processes had negative impacts on the firm. Our findings have implications for organizations regarding how they could restructure their internal practices and contain the fallout after a data breach.